Antigone and her siblings. On “La tumba de Antígona” by María Zambrano (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2021)
In this contribution, we want to examine the concept of brotherhood that Maria Zambrano develops in her play La tumba de Antígona (The Tomb of Antigone). In the long prologue, which can be read as an independent text, emphasis is led on the heroine as the sister who sacrifices herself and who, in solitude, assumes the fullness of her being. In the tragedy, that starts when the young woman has already been condemned, Ismene and Antigone, contrary to Sophocles’ model, are united. Antigone makes no distinction between Eteocles and Polynices and reproaches them for their lack of brotherhood. Polynices then launches the utopian vision of the “city of the brothers” in which there are neither fathers nor sons and there is no room for sacrifice. Although at the end of the play, the protagonist is taken to the promised land of love, we have reason to believe that it does not coincide with the “city of the brothers”, neither in the personal nor in the political dimension. Antigone and Ismene already put in practice the values of freedom, equality, and fraternity. The city desired by Zambrano, could it be “the city of the sisters”?
Keywords: María Zambrano; Antigone; fraternity